2016
DOI: 10.1093/mnras/stw1426
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric estimation of morphological lopsidedness

Abstract: Asymmetries in the neutral hydrogen gas distribution and kinematics of galaxies are thought to be indicators for both gas accretion and gas removal processes. These are of fundamental importance for galaxy formation and evolution. Upcoming large blind H i surveys will provide tens of thousands of galaxies for a study of these asymmetries in a proper statistical way. Due to the large number of expected sources and the limited resolution of the majority of objects, detailed modelling is not feasible for most det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…We create the bias image by placing the SoFiA source mask in a section of the spectral cube not containing any H i signal and integrating the signal in each voxel in the mask to create a moment 0 image. Giese et al (2016) showed that the bias-corrected asymmetry, A map , provides a lower limit on the intrinsic asymmetry and that the asymmetry can be better determined using machine learning and a library of model galaxies, however this is beyond the scope of the current work. We illustrate the calculation for a noiseless model galaxy, the model rotated by 180 • and the absolute residuals which are then summed (left, centre and right panels of Fig.…”
Section: Moment 0 Asymmetrymentioning
confidence: 95%
See 2 more Smart Citations
“…We create the bias image by placing the SoFiA source mask in a section of the spectral cube not containing any H i signal and integrating the signal in each voxel in the mask to create a moment 0 image. Giese et al (2016) showed that the bias-corrected asymmetry, A map , provides a lower limit on the intrinsic asymmetry and that the asymmetry can be better determined using machine learning and a library of model galaxies, however this is beyond the scope of the current work. We illustrate the calculation for a noiseless model galaxy, the model rotated by 180 • and the absolute residuals which are then summed (left, centre and right panels of Fig.…”
Section: Moment 0 Asymmetrymentioning
confidence: 95%
“…Giese et al (2016) found that the signal to noise ratio (SNR) affects the reliability of the optical parameters when applied to H i maps, with low SNR data not producing meaningful results. Accounting for SNR, Giese et al (2016) found the Conselice et al (2000) asymmetry to be the only parameter to provide useful information for measuring deviations away from a symmetrical disk. Hence from the optical morphology parameters we only consider the Conselice et al (2000) asymmetry.…”
Section: Spatially Resolved Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…By characterizing the global H I spectra of around half a million galaxies, we will obtain a wealth of properties, including their systemic and rotational velocities, H I and total dynamical mass estimates, and their profile shape. The latter can be an excellent indicator of environmental effects, with highly symmetric H I profiles typically found in isolated spiral galaxies (Espada et al 2011) and asymmetric H I profiles in galaxies affected by tidal interactions and/or ram pressure stripping (Giese et al 2016;Scott et al 2018). (right).…”
Section: Environment-driven Galaxy Evolutionmentioning
confidence: 99%
“…With observed average SFRs of ∼ 3 yr −1 (Bothwell et al 2011) in the local universe it is clear that a typical massive galaxy would use up its gas supply within a few Gigayears if the gas is not replenished or recycled (Kennicutt et al 1994). Besides the SFRs, continuous accretion of gas onto the disc of spiral galaxies can also serve to explain other observed phenomena, such as asymmetries of galactic discs (van Eymeren et al 2011;Giese et al 2016) and warping (García-Ruiz et al 2002) or the chemical composition of the galactic discs (Chiosi 1980). Up to now observations of ongoing accretion have remained elusive in the sense that not enough accretion events are observed to explain the required accretion rates (Sancisi et al 2008).…”
Section: Introductionmentioning
confidence: 99%